Analysis of Factors Affecting Followers Purchase Intention on Instagram Social Media - Sagita Putra, Mochammad Aribowo Adi; Wulandari, Eka Putri (Jurnal Ilmiah Manajemen & Bisnis, 2023)
The primary objective of this research is to examine the influence of influencer characteristics on the purchase intentions of their followers on the Instagram social media platform. This study employs a research model predicated on the previous work, encompassing the following variables: homophily, physical attractiveness, social attractiveness, trust, expertise, parasocial relationships, and purchase intentions. A purposive sampling approach was utilized in this study, comprising 225 respondents who were interviewed. Data collection was conducted through an online questionnaire distributed via Google Form on social media. The respondents included Instagram social media users aged 17 or older who follow and have encountered reviews from fashion influencers. Data analysis was performed using the Structural Equation Modelling (SEM) technique, specifically the Partial Least Square (PLS) method. The findings of this research reveal that the homophily attitude variable exerts a positive influence on trust, expertise, and parasocial relationships. Similarly, the physical attractiveness variable demonstrates a positive impact on trust, expertise, and parasocial relationships. Additionally, the social attractiveness variable exhibits a positive impact on trust, expertise, and parasocial relationships. Furthermore, the variables of trust, expertise, and parasocial relationships are positively associated with purchase intentions.